Analisis Tekstual Kata ‘Kalian’ (ὑμῶν) atau ‘KAMI’ (ἡμῶν) Dalam Kolose 1:7 - Harman Ziduhu Laia (Sekolah Tinggi Teologi Sola Gratia Indonesia, 2023)
One of the textual problems in Colossians 1:7 concerns whether the Apostle Paul as the original writer of the letter to the Colossians wrote the variant ὑμῶν (you/your) or the variant ἡμῶν (us/our) in the clauses ὅς ἐστιν πιστὸς ὑπὲρ [ὑμῶν or ἡμῶν?] διάκονος τοῦ Χριστοῦ. Scholars have defended both variants. Textual analysis of external evidence considerations suggests that the ἡμῶν (us/our) reading variant has earlier and more authoritative witnesses. On the other hand, internal evidence analysis, namely from context, structural, and exegetical considerations, support the ἡμῶν (us/our) reading variant and does not allow for the possibility of the ὑμῶν (you/your) reading variant being the original. Thus, the transmission of ἡμῶν to ὑμῶν may be due to a homoioarcton error and harmonization correction. So the original clause is ὅς ἐστιν πιστὸς ὑπὲρ ἡμῶν διάκονος τοῦ Χριστοῦ (who is a faithful minister of Christ on our/us behalf), emphasizing that Epaphras was Paul and Timothy's representative in serving the Colossians. ABSTRAK BAHASA INDONESIA Salah satu persoalan tekstual dalam Kolose 1:7 adalah mengenai apakah rasul Paulus sebagai penulis asli surat Kolose menulis varian ὑμῶν (kalian) atau varian ἡμῶν (kami) dalam klausa ὅς ἐστιν πιστὸς ὑπὲρ [ὑμῶν atau ἡμῶν?] διάκονος τοῦ Χριστοῦ. Masing-masing para sarjana telah mempertahankan kedua varian itu. Kritik tekstual dari pertimbangan bukti eksternal menunjukkan bahwa varian bacaan ἡμῶν (kami) memiliki saksi yang lebih awal dan otoritatif. Di sisi lain, analisis bukti internal, yakni dari pertimbangan konteks, struktural, dan eksegetikal mendukung varian bacaan ἡμῶν (kami), dan tidak memungkinkan varian bacaan ὑμῶν (kalian) sebagai asli. Jadi, dimungkinkan bahwa transmisi ἡμῶν ke ὑμῶν disebabkan oleh kesalahan homoioarcton dan koreksi harmonisasi. Jadi klausa aslinya adalah ὅς ἐστιν πιστὸς ὑπὲρ ἡμῶν διάκονος τοῦ Χριστοῦ (yang demi kami adalah pelayan Kristus yang setia), dengan penekanan bahwa Epafras adalah perwakilan Paulus dan Timotius dalam melayani jemaat di Kolose.